Beatrice, Laura, and the Others: The Fin de Siècle Debate on Female Inspirers and the Popularising Turn of Giovanni Federzoni and Eugenia Codronchi (Sfinge) - Arianna De Gasperis (Humanities)
Between the late-nineteenth and the early-twentieth centuries, Beatrice and Laura, as literary characters and beloved women of Dante and Petrarch, were at the centre of a vigorous scholarly debate, which gained traction in Romagna’s literary circles. Offering a comparative analysis of two key case studies—La vita di Beatrice Portinari (1904) by Giovanni Federzoni, and Laura’s biographical profile from Femminismo storico (1901) by Sfinge (Eugenia Codronchi Argeli)—this article reconstructs the popularising turn of this debate and its effect on medieval female characters’ reception as poetic inspirers. While Federzoni is motivated by didactic aims, seeking to facilitate readers’ access to the Commedia by deconstructing Beatrice’s abstraction, Sfinge elevates Laura as a model for contemporary women. Through an accessible structure and a hybrid methodology blending historical inquiry with literary imagination, both authors challenge allegorical readings and reclaim Beatrice and Laura as historically grounded figures.